PREFERENSI PELETAKAN TELUR DAN PENGHAMBATAN PERKEMBANGAN PRADEWASA NYAMUK Aedes aegypti L. DI BERBAGAI MEDIA AIR - Makna Fathana Sabila; Rully Rahadian; Jafron Wasiq Hidayat (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2013)
Water media influences the effectiveness of the use of ovitrap media for Ae. aegypti. Water media which is prefered by the mosquito as well as inhibition the premature growth have huge potency in controlling Ae. aegypti. The objective of this study were to investigate the preference of oviposition of Ae. Aegypti and to determine the premature growth of Ae. aegypti in water media containing a combination of organic matter and different chlorine concentrations, also to examine the interaction between organic matter and chlorine to the preferences of oviposition and the premature growth of Ae. Aegypti. The method of this study is done by experiment by applying Completely Randomize Design (RAL). This study used two types of water media combination. The media combinations contained organic materials and chlorine with seven different treatments. They were well water (control), water added with soil and hay-soaked water added with chlorine by 5, 10, and 15 ppm respectively. The findings show that Ae. aegypti have the tendency in choosing hay-soaked water in lay the eggs since it has abundant content of organic matter in it. The mean amount of Ae. aegypti oviposition in the water medium combination ranged from 84 to 152.7 eggs, while the percentage of premature survival rate ranged from 59.4% to 97%. In conclusion, the study showed that the preference of oviposition is highly influenced by the organic matter content of the media. Both organic matter and chlorine do not inhibit the premature growth of Ae. aegypti. However, the interaction between organic matter and chlorine to the preferences of oviposition and the premature growth of Ae. aegypti was not found. Keywords: Aedes aegypti, combination, ovitrap, organic matter, chlorine.